2020
DOI: 10.1175/jhm-d-19-0104.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Turbulent Heat Fluxes via Assimilation of Air Temperature and Specific Humidity into an Atmospheric Boundary Layer Model

Abstract: A number of studies have used time series of air temperature and specific humidity observations to estimate turbulent heat fluxes. These studies require the specification of surface roughness lengths for heat and momentum (that are directly related to the neutral bulk heat transfer coefficient CHN) and/or ground heat flux, which are often unavailable. In this study, sequences of air temperature and specific humidity are assimilated into an atmospheric boundary layer model within a variational data assimilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…The key unknown parameters of this model are the dimensionless neutral bulk heat transfer coefficient, C HN (‐), and the soil and canopy evaporative fraction, EF s (‐) and EF c (‐), respectively. C HN accounts for the effect of the roughness length for momentum and sensible heat fluxes (Caparrini et al, 2003; Tajfar et al, 2020). EF s and EF c scale the partitioning of available energy between sensible and latent heat fluxes and are affected by soil moisture conditions and vegetation cover (Caparrini et al, 2004b; Lu et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The key unknown parameters of this model are the dimensionless neutral bulk heat transfer coefficient, C HN (‐), and the soil and canopy evaporative fraction, EF s (‐) and EF c (‐), respectively. C HN accounts for the effect of the roughness length for momentum and sensible heat fluxes (Caparrini et al, 2003; Tajfar et al, 2020). EF s and EF c scale the partitioning of available energy between sensible and latent heat fluxes and are affected by soil moisture conditions and vegetation cover (Caparrini et al, 2004b; Lu et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Given the abovementioned shortcomings of the existing VDA approaches, Tajfar et al [81] developed a VDA approach that estimates H and LE by assimilating sequences of reference-level air temperature and specific humidity (i.e., state variables of the atmosphere) into an atmospheric boundary layer (ABL) model. The main unknowns of the Tajfar et al [81] VDA approach are the neutral bulk heat transfer coefficient (C HN ) (that scales the sum of H and LE) and evaporative fraction (EF) (that scales the partitioning of available energy between H and LE).…”
Section: Introductionmentioning
confidence: 99%
“…Given the abovementioned shortcomings of the existing VDA approaches, Tajfar et al [81] developed a VDA approach that estimates H and LE by assimilating sequences of reference-level air temperature and specific humidity (i.e., state variables of the atmosphere) into an atmospheric boundary layer (ABL) model. The main unknowns of the Tajfar et al [81] VDA approach are the neutral bulk heat transfer coefficient (C HN ) (that scales the sum of H and LE) and evaporative fraction (EF) (that scales the partitioning of available energy between H and LE). Tajfar et al [81] tested their VDA approach only at a grass-dominated sub-humid site in Kansas, and showed that sequences of the reference-level air temperature and specific humidity have implicit information for constraining C HN and EF, and retrieving turbulent heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the eddy covariance method has some restrictions that limit its applicability: (i) it requires constant supervision and maintenance, (ii) measurements in complex terrain are challenging because of the theoretical assumptions to transform the high-frequency measurements to turbulent fluxes [5], and (iii) because of extensive data quality requisites, gaps are inevitable, particularly under low turbulence mixing conditions [6,7]. Because of these difficulties, efforts have been made to parameterise them based on more commonly measured variables [8][9][10][11][12][13] and to compare among different methods to estimate and measure these fluxes [14][15][16][17][18]. One of the most frequently used approaches is to follow the work of [19] and [20], which relates the average temperature, humidity, and wind speed profiles in the boundary layer to the turbulent fluxes.…”
Section: Introductionmentioning
confidence: 99%